IMPLEMENTASI METODE TAKRAR DALAM PEMBELAJARAN MENGHAFAL AL-QUR’AN - Fithriani Gade (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
To recite the verses of al-Qur’an repeatedly and arrangeably is an appropriate way to maintain and to bear in mind in such for a long time. In line to this, the method of takrar is strongly believed as the proper way. The implementation of the method of takrar is closely to deal with the learning method to achieve the target. By doing so, the process of bearing in mind the verses of al-Qur’an cannot be simply separated from one’s memories happened in the past and can be re conjured up through that way. The method of takrar is much easier to do by reciting the verses gradually and repeatedly to achieve maximum target. In fact, this process is strongly to do with the process of teaching taught by the angel Gabriel to the prophet Muhammad (peace be upon Him). For the time being, the prophet was illiterate and Gabriel insisted the prophet recite the verses till three times but it eventually did not work. After all, the angel kept teaching him to recite them more and more and finally it worked. In addition, the implementation of the method of takrar is aimed at sustainably maintaining the purity and the existence of al-Qur’an besides having other three functions among other things are to receive self-learning, to produce self-learning and to secure self-learning.